Faktor Yang Berhubungn Dengan Kejadian Dismenore Primer Pada Mahasiswi Universitas Dian Nuswantoro Semarang - Ika Setiani; Vilda Ana Veria Setyawati (Dian Nuswantoro Semarang, 2016)
Dysmenorrheal or menstrual disorders are problems experienced by women and may interfere their activities. The study that was done on students of Faculty of Nursery Science of Padjajaran University class of 2011 shows that 94 of 104 students encounter primary dysmenorrheal which the age range of the student about 19-21 years old which are continuing study in university. Dian Nuswantoro University has female population more than male, so dysmenorrheal can be happened on them. The purpose of this study was to analyze factors associated with the incidence of primary dysmenorrheal on students of Dian Nuswantoro University.This was observational analytic study with a quantitative method and cross sectional approach. The chi square test and prevalence ratio was used for data analysisThe results showed that there was no relationship between smoking behavior with the incidence of primary dysmenorrheal (p-value = 0.798). There was no relationship between the behavior of consuming alcohol with the incidence of primary dysmenorrheal (p-value = 0.448). There was no relationship between consumption of junk food with the incidence of primary dysmenorrheal (p-value = 0.334).Students could minimaze primary dysmenorrheal when they have menstruation by decreasing the habitual activity that is causing primary dysmenorrhea such as smoking behavior, onsuming alcohol, and junk food.Keyword: primary dysmenorrheal, smoking habit, alcohol consumption, junk food